TINGKAT KESEMBUHAN TB PARU PADA ANAK BALITA YANG MENDAPAT SUPLEMENTASI VITAMIN A DOSIS TINGGI - Susi S. Suwardi; Muherdiyantiningsih Muherdiyantiningsih (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2002)
THE RECOVERY RATE OF PULMONARY TUBERCULOSIS OF THE UNDERFIVE CHILDREN SUPPLEMENTED BY HIGHDOSE VITAMIN A.Background: Tuberculosis (TB) is the most common cause of death among other Infection disease. It Is recognized thattuberculosis affects various age groups, Including underfive children. The complete and fast treatments are needed to reduce the prevalence and Incidence of TB in the communities. Considering the role of vitamin A In reducing the severely of Infection, supplementation of hlghdose (200.000 IU) vitamin A in every two months for 6 months will be helpful to increase recovery rate of pulmonary tuberculosis.Design: This study was conducted at the hospital in Bogor region. Sample size was 66 children of underfive years old, whowere suffered pulmonary TB according to Mantoux test, clinical examination, and chest x-ray (CXR). Physical examination, morbidity, and anthropometric data were assessed every month. Food consumption recall, serum vitamin A concentration, hemoglobin content, hematocrit, blood sedimen rate (BSR), and CXR were assessed at 0 and 6 months. The children wererandomly assigned to either vitamin A-supplemented (AS, n=33) group or vitamin A-unsupplemented (AUS, n=37). All of the children were treated by isoniazide, ethambutol and rifampicin. The recovery rate was assessed according to the score of 3 variabels: nutrition status, BSR, and CXR.Results: Nutrition status and hemoglobin increased significantly in both groups (p<0,05). The clinical symptoms subsided and BSR decreased in both groups, but was not significant different between groups. The CXR data showed there were improvement in 84,5% of AS group and 67,7% of AUS group. There were scoring improvement of the recovery rate in bothgroups, but was not significant different between groups.Conclusions: There was significant relation between vitamin A status and the recovery rate of pulmonary tuberculosis, but was not significant different between groups.Keywords: tuberculosis, vitamin A supplementation, recovery rate